2022
DOI: 10.3390/ijms23010498
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Steatohepatitis (NASH) and Organokines: What Is Now and What Will Be in the Future

Abstract: Non-alcoholic steatohepatitis (NASH) is characterized by steatosis, lobular inflammation, and enlargement of the diameter of hepatocytes (ballooning hepatocytes), with or without fibrosis. It affects 20% of patients with non-alcoholic fatty liver disease (NAFLD). Due to liver dysfunction and the numerous metabolic changes that commonly accompany the condition (obesity, insulin resistance, type 2 diabetes, and metabolic syndrome), the secretion of organokines is modified, which may contribute to the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 106 publications
2
32
0
1
Order By: Relevance
“…The reduced regulators of inflammatory genes observed in the tissues of BEZ-treated animals are in line with previous findings, which showed that BEZ attenuates inflammatory processes [33,34]. FGF21 and adiponectin are described as insulin sensitizers, and a high leptin level is associated with insulin resistance [35]. BEZ activated FGF21 and adiponectin upstream regulators, as well as inhibited leptin.…”
Section: The Bez-modified Transcriptional Profilesupporting
confidence: 91%
“…The reduced regulators of inflammatory genes observed in the tissues of BEZ-treated animals are in line with previous findings, which showed that BEZ attenuates inflammatory processes [33,34]. FGF21 and adiponectin are described as insulin sensitizers, and a high leptin level is associated with insulin resistance [35]. BEZ activated FGF21 and adiponectin upstream regulators, as well as inhibited leptin.…”
Section: The Bez-modified Transcriptional Profilesupporting
confidence: 91%
“…Its production is controlled by food intake, sex hormones, energy status, and inflammatory mediators. Leptin can also modulate both the innate and adaptive immune systems by activating proliferation and activation of macrophages and monocytes, regulating the cytotoxicity of natural killer cells, modulating neutrophils chemotaxis, and controlling T CD4, Th1 (T helper 1), and Th2 (T helper 2) cells’ phenotypes [ 11 , 99 , 100 , 101 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%
“…In turn, FGF-21 can decrease the activity of both cellular and humoral immune responses in individuals affected by RA. To maintain joint integrity, FGF-21 blocks the production of cathepsin K and metalloproteinases, especially the MMP-3 [ 11 , 122 , 123 , 124 , 125 , 126 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%
See 2 more Smart Citations